Peningkatan Keterampilan Berpikir Kritis Dan Pemahaman Hak Dan Kewajiban Melalui Model Problem Based Learning Pada Siswa Kelas I MIS Tahfizh Rabbani Kota Solok - Anggraini, Rini; Rika Afriani, Vino (Journal of Development Education and Learning (JODEL), 2025)
Civic Education on rights and obligations in Grade I at MIS Tahfizh Rabbani was hindered by one-way teaching, making it difficult for students to grasp abstract concepts and think critically. This two-cycle classroom action research applied Problem-Based Learning (PBL) to improve these skills. The subjects were 15 students, with data collected through observation, interviews, and student work analysis. Results showed improvement in critical thinking from 13.3% in the pre-cycle to 53.3% in Cycle I, and 80% in Cycle II. Students also demonstrated a deeper understanding of rights and obligations. PBL proved effective in fostering student-centered learning, enhancing critical thinking, and strengthening conceptual understanding.